Growth performance, visceral organ weights, and gut health of weaned pigs fed diets with different dietary fiber solubility and lipid sources. (17th October 2021) - Hong, Jinsu; Ndou, Saymore Petros; Adams, Seidu; Scaria, Joy; Woyengo, Tofuko Awori
Abstract: The objective of this study was to determine the interactive effects of dietary fiber solubility and lipid source on growth performance, visceral organ weights, gut histology, and gut microbiota composition of weaned pigs. A total of 280 nursery pigs [initial body weight (BW) = 6.84 kg] weaned at 21 d were housed in 40 pens (7 pigs/pen). The pigs were fed four diets (10 pens/diet) in a randomized complete block design in two phases: Phase 1 from 0 to 2 wk and Phase 2 from 2 to 5 wk. The diets were corn-soybean meal-based with either sugar beet pulp (SBP) or soybean hulls (SBH) as a fiber source and either soybean oil (SBO) or choice white grease (CWG) as a lipid source in a 2 × 2 factorial arrangement. The BW and feed intake were determined by phase, whereas visceral organ weights, intestinal histology, and gut microbial composition were determined at the end of the trial. Dietary fiber solubility and lipid source did not interact ( P > 0.05) on average daily feed intake and average daily gain across all phases. However, the gain to feed ratio (G:F) for CWG-containing diets was lower ( P < 0.05) than that for SBO-containing diets for Phase 1. Also, G:F for SBP-containing diets was lower ( P < 0.05) than that for SBH-containing diets for Phase 1 and for the entire study period. Pigs fed SBP-containing diets had greater ( P < 0.05) stomach weight, and tended to have greater ( P < 0.10) small and large intestine weights relative to BW than those fed SBH-containing diets. Duodenal villous height to crypt depth ratio for CWG-based diets tended to be greater ( P = 0.09) than that for SBO-based diets. Fiber solubility and lipid source interacted ( P < 0.05) on relative abundance of Bacteroides in the colon such that the relative abundance of the Bacteroides for CWG was greater ( P < 0.05) than that for the SBO in SBP-based diet, but not in SBH-based diet. Relative abundance of Butyricicoccus in the colon for SBH-based diet was greater ( P < 0.05) than that for SBP-based diet. In conclusion, inclusion of SBH instead of SBP in corn-soybean meal-based diets for weaned pigs can result in increased feed efficiency and relative abundance of Butyricicoccus in the colon, which is associated with improved gut health. Also, inclusion of SBO instead of CWG in the diets for weaned pigs can result in improved feed efficiency during Phase 1 feeding; however, the pigs may recover from the low feed efficiency induced by dietary inclusion of CWG instead of SBO after Phase 1 feeding.